THE ETHICAL IMPLICATIONS OF REMOTE ROBOTIC SURGERY: WHO CONTROLS THE SCALPEL? - KAMALOVA NASIBA BAKHTIYOROVNA; B.A. Umarov (Ta’lim innovatsiyasi va integratsiyasi, 2025)
ABSTRACT Remote robotic surgery has introduced groundbreaking advancements in modern healthcare, allowing expert surgeons to operate on patients from thousands of kilometers away. While this innovation offers increased access to specialized care, especially in underserved regions, it also raises complex ethical questions. Who bears responsibility if a complication arises during a remote procedure? How is informed consent managed when the surgeon and patient have never met face-to-face? What safeguards are in place to prevent system failures or cyber interference? This paper explores the moral, legal, and practical implications of remote-controlled surgical procedures, focusing on accountability, patient autonomy, data privacy, and the evolving relationship between human judgment and machine precision in life-or-death situations.